The strategic learning (Revista Electrónica REDINE, 2018)
One of the aims of the education is her of teaching the pupils to whom there turn autonomous, independent apprentices and autorregulados, capable of learning to learn, situation that can be achieved on having endowed the pupil of tools or cognitive instruments that serve him to face pos if same new situations of learning belonging to different domains and useful before the most diverse situations. The possibility of the student of learning to learn, proves to be increasingly conscious of his process of cognition, that is to say, of the metacognición process that refers to the knowledge or conscience that has the person of his own mental processes, on as learns and to the control of the cognitive domain, on his way of learning. Both are orientated to the service of an improvement of the personal study that leads him to satisfactory results of learning
Keywords: metacognición; strategic learning; autonomous learning